Cycle life prediction of NiCo2O4//activated carbon asymmetric supercapacitors. (September 2022) - Wang, Hongzhi; Bao, Saisai; Sun, Shaofeng; Zhang, Weiguo; Su, Zhan; Yu, Jinshan
Abstract: Here, we report that the NiCo2 O4 nanoflower-spherical material, which has a specific capacitance of 1503 F g −1 at the current density of 1 A g −1, is synthesized by the hydrothermal method. And asymmetric supercapacitors (ASCs) of NiCo2 O4 //activated carbon (AC) exhibit the energy density of 25.02 Wh kg −1 at a power density of 760 W kg −1 . Furthermore, to investigate the impact of aging factors on the cycle life of ASCs, a new model for capacitance life prediction is established. The model takes the cycle times, temperature, current density, and potential window into account, which is based on the classic Eyring's law and the actual specific capacitance of ASCs. It forecasts that the ASCs will have a cycle life of 9750 cycles under ideal condition of 25 °C, 5 A g −1 current density, and 0–1.5 V potential range, with only a relative error of −0.09 % and a root mean square error (RMSE) of 5.47 %, compared to the actual life of 9759 cycles. Therefore, this model provides a strong basis for the life prediction and optimization of asymmetric supercapacitors. Highlights: A high-performance asymmetric supercapacitor of NiCo2O4//AC is assembled. The SOC of asymmetric supercapacitors is crucial parameter. A pairwise comparative method assisted by orthogonal experiment is proposed. A new model of life prediction based on the Eyring's law is established. This modeling method provides a new idea for life prediction of pseudocapacitors.